The Self-Determination Theory and Mathematics Motivation: Grade Levels and Gender Differences among United Arab Emirates Students - Jalal Haj Hussien (Sultan Qaboos University, 2011)
The objective of this study was to investigate the impact of students' grade levels, gender, and interaction between the two on mathematics motivation. In addition, the relationship between students' various types of mathematics motivation and achievement were examined. Four hundred twenty four elementary school students (186 boys and 238 girls), 588 middle school students (296 boys and 292 girls), and 276 high school students (154 boys and 122 girls) completed the MMS. The findings of this study showed that all types of motivation in mathematics steadily decreased with grade advancement (elementary through high school) with the exception of introjected regulation. Moreover, results indicated a significant gender difference in each type of mathematics motivation, exception regarding intrinsic motivation, where the difference was not significant. In addition, the interaction between grade levels and gender was significant only in students' introjected regulation; the differences in intrinsic, external regulation, and amotivation were consistent between males and females in different grade levels. Finally, the results revealed a significant relationship between all types of motivation and mathematics achievement as well as overall academic achievement.